PENGEMBANGAN MEDIA DIORAMA UNTUK ANAK USIA DINI DI TK BINA KASIH KECAMATAN GALANG - Shola Ningsih; Novita Frizka (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This development research aims to determine the suitability of learning media, namely Diorama media, in early childhood learning activities. This research is a type of research and development (R&D) with the ADDIE model. The focus of this research is the development of diorama media to make it easier for teachers to create and use diorama media, and diorama media is also easy for young children to understand. The instrument used to collect data is a questionnaire or questionnaire given to validators, namely material expert validators and media expert validators. Interview instruments were given to teachers before and after using the diorama media developed in this research. Based on the validation results from the material expert validator, a score of 76.3% was obtained in the "Decent" category, and the results from the media expert validator obtained a score of 98.4% in the "Very Eligible" category. This proves that this diorama media is very suitable and safe to use in early childhood learning activities. The results of teacher interviews also stated that diorama media was suitable for use in early childhood learning activities. Based on the assessment score criteria, it can be said that the Diorama Media Development for Early Childhood that has been developed is valid and very suitable for use in the early childhood learning process.